1992
DOI: 10.1007/bf00024427
|View full text |Cite
|
Sign up to set email alerts
|

Pollination-induced flower senescence: a review

Abstract: Ethylene has long been implicated in the control of the senescence of many cut flower species, but the control of senescence in relation to wild species has received much less attention. The longevity of individual flowers varies greatly from species to species; in some each flower is open for just a few hours, whilst in others the flower may persist for several weeks, or even months. The functional life of the flower may be terminated by petal wilting, abscission or a colour change of all, or part, of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 39 publications
1
85
0
1
Order By: Relevance
“…Indeed, there are a number of reports that auxin is a natural component of orchid pollen (Müller, 1953;Arditti, 1979;Stead, 1992). In light of this association between auxin and pollination in orchids, we also examined the effect of auxin on the stimulation of ethylene produced by detached flowers.…”
Section: Physiology Of the Pollination Response And The Involvement Omentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are a number of reports that auxin is a natural component of orchid pollen (Müller, 1953;Arditti, 1979;Stead, 1992). In light of this association between auxin and pollination in orchids, we also examined the effect of auxin on the stimulation of ethylene produced by detached flowers.…”
Section: Physiology Of the Pollination Response And The Involvement Omentioning
confidence: 99%
“…Pollination responses have been studied in a number of flowers mainly with regard to pollen tube/style interactions (Nasrallah et al, 1985(Nasrallah et al, ,1988Anderson et al, 1986;Bernatsky et al, 1987;Cornish et al, 1987;Sanders and Lord, 1989;Haring et al, 1990), with only a few focusing on pollination-induced perianth senescence (reviewed by Halevy, 1986;Stead, 1992). Because pollen germinates on the stigma but subsequent developmental responses occur in the ovary and perianth, a pollination signal must move from the stigma to other floral organs, thus implicating the involvement of an interorgan messenger of pollination.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen tubes eventually reach the ovary, each of them enters an ovule to deposit the male gametes into the embryo sac for fertilization (Cheung, 1995;Knox, 1984;Mascarenhas, 1993). Pollination induces many physiological and developmental responses within the flower, including ethylene evolution, stylar and perianth senescence, and changes in the nectary, ovary and ovules (Halvey, 1986;Herrero, 1992;Larsen et al, 1993;Stead, 1992;Zhang and O'Neill, 1993). Pollination also causes dramatic cellular and biochemical responses in the pistil, leading to deterioration and death in specific cell types (Cresti et al, 1986;Herrero and Dickinson, 1979;Fisher, 1968, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, orchid pollen contains high levels of indoleacetic acid (Müller, 1953;Arditti, 1971;Stead, 1992), leading investigators to associate the response to pollination with auxin. Many studies have demonstrated that the application of a number of auxins to the orchid stigma partially substitutes for pollination in inducing the postpollination syndrome in orchid flowers (Curtis, 1943;Burg and Dijkman, 1967;Arditti and Knauft, 1969;Arditti, 1979;Strauss and Arditti, 1982).…”
Section: Introductionmentioning
confidence: 99%